Unveiling the cellular and molecular mode of action of Melaleuca cajuputi Powell. essential oil against aflatoxigenic strains of Aspergillus flavus isolated from stored maize samples. (August 2022) - Chaudhari, Anand Kumar; Singh, Vipin Kumar; Das, Somenath; Kujur, Anupam; Deepika,; Dubey, Nawal Kishore
Abstract: This study aimed to reveal the bio-efficacy of Melaleuca cajuputi essential oil (McEO) against aflatoxigenic fungi and lipid peroxidation causing deterioration of stored maize samples. Three different toxigenic strains of Aspergillus flavus, namely AF-LHP-M2, AF-LHP-SP2, and AF-LHP-VS8 were investigated. Gas chromatography-mass spectrometry (GC-MS) analysis of EO revealed the presence of α-pinene (49.24%) as major compound. Investigation on efficacy showed that McEO exhibited remarkable inhibitory activity against growth and AFB1 production by AF-LHP-M2 (2.0 and 1.4 μL mL −1, respectively), AF-LHP-SP2 (1.2 and 1.0 μL mL −1, respectively), and AF-LHP-VS8 (0.8 μL mL −1 ) ( p  < 0.05). The McEO inhibited fungal growth via inhibition of ergosterol biosynthesis, cellular constituents' leakage, and damage of mitochondrial membrane potential, while AFB1 production by inhibition of intracellular methylglyoxal. Further, molecular docking study was carried out to unveil the binding affinities of major compounds with the target protein Nor-1 (primarily catalyze an important step in AFB1 biosynthesis), and the results revealed good correlation with the experimental findings. In addition, McEO showed significantly ( p  < 0.05) higher DPPH and ABTS + scavenging activity with IC50 values 3.16 and 4.29 μL mL −1, respectively. Interestingly, McEO inhibited AFB1 production, and malondialdehyde content in fumigated maize samples without significantly ( p  < 0.05) changing their sensory attributes, ascertaining its efficacy in food system with high safety profile (LD50  = 1800 mg kg −1 body weight) on mice model. The overall results proved McEO's potential as natural food preservative of stored food products. Graphical abstract: Image 1 Highlights: Melaleuca cajuputi essential oil (McEO) was characterized through GC-MS analysis. McEO inhibited the mycelial growth and aflatoxin production of three tested fungi. Molecular docking was performed to decipher the experimental results. McEO effectively reduced aflatoxin accumulation and lipid peroxidation in maize. McEO displayed non-toxic profile in mammalian (mice) system.